(untitled) - Dawson, William Harbutt (London, 1908)
William Harbutt Dawson was one of the 20th century's foremost historians on Europe, particularly Germany. He wrote several comprehensive histories of Germany, both modern and ancient, and this is one of his most critically acclaimed.
Keywords: Công nghiệp; Nước Đức,Germany